Gender equality and women empowerment: key elements to sustainable rural development in Nigeri (2014)
Women Empowerment and gender equality are key elements lo sustainable rural development. Globally women empowerment has been a subject of discussion in both developed and developing countries when it comes to national and local development. This paper examined Gender Equality and Women Empowerment: Key Elements to Sustainable Rural development. The research was carried out in Akinyele Local Government Area in Oyo State. The target population for the study was rural women in Akinyele Local Government Area of Oyo State. The purposive sampling techniques were adopted in selecting the 120 respondents. Questionnaire was designed to elicit responses from the subjects. The data collected were analysed using Pearson product moment correlation Statistical tool. The findings show that there is a significant relationship between women empowerment. gender equality and sustainable rural development (r- tabulated = 0.178 < r calculated =0.301 and p< 0.05. also Gender Equality and Sustainable Rural Development/Nation Building (r-tabulated = 0.424 < r calculated = 0.501 and P< 0.05.) In conclusion, this paper legitimises women's Status and contributes immensely to the awareness of their major contributions in communities